Guaranteeing prescribed performance fast tracking control of air-breathing hypersonic vehicles. (October 2020) - Cheng, Zian; Chen, Fuyang; Hu, Kaiyu
This paper investigates a fast-tracking controller with prescribed performance for flexible air-breathing hypersonic vehicles subject to uncertain parameters, external disturbances, actuator faults and backlash non-linearity. For the velocity and altitude dynamics, a prescribed performance control scheme is respectively utilized to provide preselected bounds on the transient and steady characteristics of tracking errors, also it can effectively relieve the constraint of scramjet on the angle of attack. A sliding mode exact observer is introduced to estimate the lumped disturbance, meanwhile the analytic differential computation on virtual controllers is avoided in the back-stepping design for altitude tracking. Based on prescribed performance control and sliding mode exact observer, the non-singular fast terminal sliding mode technology is introduced to design a control law, which is capable of ensuring both velocity and altitude tracking errors converge into the prescribed sets in finite-time. Simulations on the high-fidelity air-breathing hypersonic vehicle mode are implemented to highlight the effectiveness of the developed controller.